Athlete profiles along grit, sport orientation and sport persistence based on a quantitative research on Hungarian athletes - Kovács, K. E. (Frontiers in Sports and Active Living, 2025)
Introduction: Sport persistence, the sustained engagement in sporting activities, is influenced by a combination of intrinsic and extrinsic motivational factors. Understanding these factors is crucial for supporting long-term athlete commitment and preventing dropout. The study examines athlete profiles based on sport persistence, sport orientation, and grit, aiming to identify distinct clusters that reveal different psychological and sociodemographic characteristics.